Investigating revisit intention of medical tourists in China through nutritional knowledge, perceived medical quality, and trust in the physiologist: A recommendation on health tourism policy measures - Fengmin, Zhai; Baijun, Wu; Jiangtao, Bai; Li, Liu; Patwary, Ataul Karim (Frontiers in Public Health, 2022)
Good medical care has long been a top priority in health tourism to keep the flow of visitors coming for medical treatment. Medical tourism encompasses a range of treatments, from basic check-ups to surgical operations. For its friendly character and high quality of service, China has earned a reputation as one of Asia's top destinations for health tourism. Along with India and Taiwan, Japan, Thailand, and South Korea are China's top tourism destinations. By considering the above fact, this study aims to examine the influence of nutritional knowledge, perceived medical quality, trust in physiologists on revisit intention of medical tourists in China. This study is cross-sectional and follows a quantitative approach. The researchers used questionnaires as a survey tool to obtain information from the respondents. The respondents of this chosen international tourists in China who come for medical treatment purposes. A systematic random sampling technique was used to select the respondents, and 315 usable responses were collected from the respondents and proceeded with further analysis. The study conducted structural equation modelling using Smart PLS version 3. The results found that nutritional knowledge perceived medical quality and trust in physiologists significantly influence the revisit intention of medical tourists in China.